The Effect Of Counseling On The Adherence Of Therapeutic Hypertension Patients - Prihanti, Gita Sekar; Sari, Novi Puspita; Septiani, Nur Indah; Tobing, Laura Putri Risty L.; Adrian, Annisa Rahayu; Ayu, Nihayatuz Rahayu; Abidin, Muhammad Zainul; Farid, Husni Puspita (University of Muhammadiyah Malang, 2020)
Failure of therapy is a result of bad adherenceÂ medication. Non-adherence to therapy is a major factor that is suspected to result in uncontrolled blood pressure in hypertensive patients resulting in more serious complications. Therefore it is important to increase the adherence rate of treatment in patients with hypertension in the treatment process. For this reason, the need for interventions to improveÂ adherenceÂ with several aspects that can be changed. This study uses One Group Pretest-Posttest Design using 100 samples. Data derived from questionnaires containing 25 items of adherence to therapy, 5 items of knowledge, 4 items of trust, 3 items of motivation, 10 items of family support with nonparametric statistical tests used were Mc Nemar test. Mc Nemar test results indicate that there is a significant difference between adherence at the pre-test and at the post-test after counseling with a significance value (p = 0,000). The results also showed that there was a difference in knowledge with a significance value (p = 0.001), motivation with a value (p = 0.031) and family support with a value (p = 0,000). The education with counseling about knowledge, trust, motivation and family support is effective in increasing compliance. There are other changeable factors such as lifestyle education, patient doctor relationships, and the use of smartphone applications for self-reported therapy can improve adherence in patients thereby minimizing therapy failure. Other educational methods that can be used besides counseling are counseling and dissemination of social media information.